2006
DOI: 10.1007/s11418-006-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Different responses of shoot and root cultures of Glehnia littoralis to yeast extract

Abstract: Differentiated shoot and root cultures of Glehnia littoralis were examined for organ-specific responses to yeast extract (YE). Growth, and changes in phenylalanine ammonia-lyase (PAL, EC 4. 1. 3. 5) activity, as well as furanocoumarin and simple phenylpropanoid production were then determined. YE affected root growth positively but negatively affected the growth of both the leaf and petiole. PAL activity was induced in all organs and reached a maximum after 2 days of treatment, though the activity in leaves wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…littoralis roots that a moderate amount of free ferulic acid and a small amount of free p-hydroxycinnamic acid were detectable after yeast-extract treatment and that these exhibited a transient increase followed by a decrease, in good agreement with the increases observed in their cell-wall-bound forms (Ishikawa et al, 2007). Elicitation by AsA under iron-deficient conditions did not lead to furanocoumarin biosynthesis, but the production of cell-wall 9 phenolics could nevertheless be increased.…”
Section: Resultssupporting
confidence: 71%
“…littoralis roots that a moderate amount of free ferulic acid and a small amount of free p-hydroxycinnamic acid were detectable after yeast-extract treatment and that these exhibited a transient increase followed by a decrease, in good agreement with the increases observed in their cell-wall-bound forms (Ishikawa et al, 2007). Elicitation by AsA under iron-deficient conditions did not lead to furanocoumarin biosynthesis, but the production of cell-wall 9 phenolics could nevertheless be increased.…”
Section: Resultssupporting
confidence: 71%
“…For example, our research group has worked to produce furanocoumarins by using in vitro cells and organs of Glehnia littoralis subjected to elicitor treatment. However, the cell cultures from our study produced only bergapten, while leaf (but not root) cultures produced both bergapten and xanthotoxin following treatment with yeast extract (YE) (Ishikawa et al 2007). Subsequent studies revealed that ascorbic acid (AsA) functioned as a powerful inducer of furanocoumarin production in organ cultures, especially in root cultures (Ishikawa et al 2008).…”
mentioning
confidence: 63%
“…Previously, we established root clones of G. littoralis using A. rhizogenes LBA9402, but none of the clones grew without ampicillin (Rahman et al 2004). Hence, in the current study, 10 clones that had been randomly selected from 100 clones were maintained in 25 ml of Murashige and Skoog (1962) (MS) basal medium supplemented with 5 mg l Ϫ1 of indole-3-butyric acid (IBA) in a 100 ml Erlenmeyer flask at 25°C and 80 rpm in the dark, with subcultures every 6 weeks, as described for normal root cultures of G. littoralis (Ishikawa et al 2007).…”
mentioning
confidence: 99%
“…In all cases, non-induced control cultures showed no enzyme activity at all. Similarly, furanocoumarins were also induced in G. littoralis white cell and shoot cultures by yeast-extract treatment (Ishikawa et al 2007;Kitamura et al 1998). …”
Section: Discussionmentioning
confidence: 96%